UPAYA PENERIMAAN PENDAPATAN ASLI DAERAH DARI SEKTOR PARIWISATA PACU JALUR DI KABUPATEN KUANTAN SINGINGI TAHUN 2018 - Oktori Lanwa; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study answers to answer the main problem about the reception of the Original Regional Receipts (PAD) of Kuantan Singingi Regency (Kuansing) from the Pacu Path tourism sector in Fiscal Year 2018. Then, find out what factors influence the acceptance of the region's original income (PAD) from the sector Runway tourism, but accepts the PAD obtained by the Kuantan Sengingi District Government each year fixing the deficit and reaching the target set. The theory used in this study is published in Policy Analysis with Research Locations in Batang Narosa Subdistrict as the center of activities and even Pacu Path Tourism in Kuantan Bay, Kuantan Singingi Regency.               The research method uses qualitative, this research is the primary data source, namely the Head of the Tourism, Youth and Sports Services Division of the Kuantan Singingi Regency, the Head of the Kuantan Singingi Regional Revenue Agency, the Kuantan Tengah District Head, the Chair / management of NGOs related to tourism, tourism aid providers and community leaders. local. Data were collected by in-depth interview techniques, observation and documentation, then the data were analyzed descriptively qualitatively. Regional Research Income of PAD Kuantan Singingi Regency's Revenue in the 2014-2018 Fiscal Year, which was obtained from the tax and retribution and licensing sectors, was also proven to have not reached the target set. Likewise with the approval of the annual Event Runway Tour Event for PAD reception in the field of tourism. Regulatory Efforts undertaken by the Regional Government include, among others, regulating Regional Regulations on Taxes and Levies as well as Business Administration, APBD fund allocation. But the acceptance of PAD was still not approved. The contributing factors are regional potential, tourist attraction and unproductive tourist attraction, limited funds and competence of regional staff to outsiders in the development of regional tourism. Keywords: Government Efforts, PAD and Pathways.